Food Culture and Well-Being Reflected in Zen Buddhist Art: A Case Study of Chongzhu Temple, Yunnan Province - Lei , Guosheng; Panthupakorn, Poradee; Chaiyakut, Pongdej (ARU Research Journal Humanities and Social Sciences, 2026)
This research aims (1) to examine the developmental stages of Zen Buddhism considering the religious and cultural values reflected in the Buddhist art of Chongzhu Temple; and (2) to analyze the food culture and well-being Practices as represented in the Buddhist art of Chongzhu Temple. A qualitative research approach was employed, including documentary research, field surveys, Buddhist art analysis, and a review of relevant literature. The findings reveal that (1) Zen Buddhism originated around the 6th century CE through the integration of Buddhist philosophy from India with Chinese culture, with Bodhidharma recognized as its principal transmitter. The core concept of Zen emphasizes direct realization of the Dharma through practice, without reliance on scriptures or textual interpretation. During the Tang Dynasty, Zen Buddhism was systematized, with an emphasis on practice in everyday life. This development led Buddhist art to shift from narrative religious storytelling toward the representation of daily life and states of spiritual practice, forming an essential context for the establishment of Chongzhu Temple and the Buddhist art within it. (2) The Zen Buddhist art of Chongzhu Temple conveys food culture and health-oriented practices through spatial structures, symbolism, and visual order. Food consumption was elevated from an ordinary daily activity to a form of meditative practice. Vegetarian food culture, tea drinking, and the ethics of mindfulness are expressed through symbolic elements such as alms bowls, bodily gestures, and the use of space, reflecting a balance between body and mind. These concepts have been reinterpreted and extended in contemporary painting, allowing the well-being practices in Zen Buddhism to be systematically explained within the framework of contemporary visual art.